From Scorching Desert to Tropical Paradise: New Form of Video Game Orientalism in Far Cry 3 - Angga Prawadika Aji (Universitas Gadjah Mada, 2021)
This paper provides an analysis of different form of orientalism found in the third title of the popular Far Cry game series. The open world system offered by Far Cry 3 brings a new nuance in the discourse of orientalism in video games, especially within the context of military shooter game. It provides both opportunities and challenges for developers to build ‘world’ as real as possible for players to explore. This construction process often reflects the orientalism practices shown by game developers in describing Eastern society and culture. Through a variety of activities such as hunting, exploring, sailing, and killing enemy forces, the player acts as a 'western mediator' who intepret the simulated Eastern world as a strange and mysterious territory.